2019
DOI: 10.1177/0145482x19869797
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Innovative Vision Simulator (OrCam) on Quality of Life in Patients with Glaucoma

Abstract: Purpose:The aim of this study was to determine the impact of OrCam on vision-related quality of life of patients with legal blindness and end-stage glaucoma. OrCam is a device comprised of a camera and earpiece attached to the user’s eyeglass that translates written text to speech.Methods:In this prospective, observational study, a total of 27 participants were recruited and tested. All participants were legally blind. Participants were provided with the OrCam device during the study period and trained how to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Similar results were found in a previous study with the OrCam, showing improvements in the ‘near vision’ subscale of the NEI‐VFQ in patients with end‐stage glaucoma (Waisbourd et al. 2019 ). As previous studies have demonstrated that the NEI‐VFQ suffers from multidimensionality, we also obtained Rasch estimates from visual functioning and socio‐emotional subscales (Stelmack et al.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar results were found in a previous study with the OrCam, showing improvements in the ‘near vision’ subscale of the NEI‐VFQ in patients with end‐stage glaucoma (Waisbourd et al. 2019 ). As previous studies have demonstrated that the NEI‐VFQ suffers from multidimensionality, we also obtained Rasch estimates from visual functioning and socio‐emotional subscales (Stelmack et al.…”
Section: Discussionsupporting
confidence: 89%
“…However, the impact of a single LVA remains unclear, as low-vision rehabilitation programmes typically offer multiple LVAs and multidisciplinary services over the course of rehabilitation. This makes it difficult to distinguish the contribution of a single device or service on a patient's rehabilitation progress (Moisseiev & Mannis 2016;Waisbourd et al 2019). Insights into the effectiveness of the OrCam will provide knowledge on which patients are most likely to benefit from the device and will also inform us on which daily activities may improve when using devices such as the OrCam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there have been studies to interpret other types of visual materials (e.g., graph, map, and picture). OrCam [28] is a voice-activated device that attaches to virtually any glasses. It helps blind users live a more independent life by processing a book text, smartphone screen, and recognize faces.…”
Section: Accessibility To Auditory Informationmentioning
confidence: 99%
“…A high-resolution camera is used to scan the characters corresponding to the finger"s touch while also reading them out loud after being scanned. After several years of research, OrCam, an Israeli company, is now developing new products that use facial recognition technology to scan not only characters but also various colors [21]. There are also "smart glasses" for people with partial vision loss.…”
Section: Character Information Recognition Systemmentioning
confidence: 99%